Techno-economic feasibility and environmental assessment of large-scale wind farms for sustainable energy generation at provincial scale of Pakistan - Hamza Ali Memon (330048); Dr. Syed Ali Abbas Kazmi (Islamabad : USPCAS-E, NUST, 2023)
TH-524
Keywords: MS EEP Thesis; MS Thesis